Smart Goggles for the Blind Using LBPH Face Recognizer - Tamiz Bharthepudy, J. Srikrishna Pradeep, A. Mohan (International Journal of Advanced Science and Technology, 2020)
Nayan, a smart goggle induced with a voice assistant, is a thought and an execution to help the blind people so that they can become an independent individual without depending on other people. Initially, Face Detection, and Gender Recognition is applied by fixing the camera module in a suitable smart goggle to detect if there is a person in the surroundings of the blind at a particular distance to help him in finding his surroundings and as a result he can notice people easily if he knows them. Secondly, the same image extracted from face detection is used to detect other applications. Thirdly, we present an algorithm for face detection, gender recognition simultaneously and other feature extractions using Local Binary Patterns Histogram (LBPH). The proposed method is called LBPH, which uses local binary operators and is easy for detection purposes due to its computational simplicity and discriminative power. The synergy among the tasks where the individual performances are boosted is exploited. After this the result is forwarded to another network and based on the probability, we give the result in the form of speech so that blind can understand his surroundings. In this work we have named the smart goggles Nayan, which is similar to Siri for iPhones and Alexa for Google.